Deskripsi Posisi Kerja berdasar Metode OWAS dan RULA: Studi Kasus Praktikum Pembuatan Baut di Laboratorium Teknik Mesin Universitas Negeri Malang - Sari, Resti Novita; Permatasari, Adelia; Prawidiastri, Firnadila; Mountaz, Lotu; Marji, Marji; Sulistyorini, Anita (Universitas Negeri Malang, 2024)
Non-ergonomic work positions can lead to fatigue and discomfort, increasing the risk of Musculoskeletal Disorders (MSDs) and injuries. This study aims to observe and describe work positions during a practical activity of bolt manufacturing among engineering students at the Faculty of Engineering. Work position assessments were conducted using the OWAS and RULA methods. Through direct observation, students were evaluated in two stages of the practical activity: winding and drilling. The results showed that the working positions of students during the practicum tended to be non-ergonomic, with OWAS scores in the threading and drilling divisions being 2 with a hazardous category for all subjects, indicating that the working posture is dangerous and requires future improvements. The RULA scores in the threading division were 6, and in the drilling division, they were 5, both in the high-risk category, suggesting the need for immediate corrective actions and changes. The conclusion of this study is that improvements in non-ergonomic working positions are necessary for industrial engineering students during bolt-making practicum activities to reduce the risk of injury, prevent MSDs, and increase productivity in the work environment.